TINJAUAN HUKUM ISLAM TERHADAP LEGALITAS ABORSI AKIBAT PERKOSAAN DALAM PP NO. 61 TAHUN 2014 - Rohmawati, R. (Ahkam: Jurnal Hukum Islam, 2015)
The issue of the Government Regulation Number 61/2014 about Reproduction Health is intended to guarantee the rights of people through the quality service. It includes safe and responsible service for mothers to produce high quality generation and reduce the number of mortality of mother. However, such regulation leads to pros and contras because it is considered that it legalizes abortion. It is clearly stated in the regulation that abortion is allowed due to some conditions such as emergency medical problem or the pregnancy because of rape. Kata kunci: Legalitas Aborsi, Perkosaan, PP No. 61 Tahun 2014, Hukum Islam